Shared music, shared occupation: Embedding music as a socio-altruistic collective- and co-occupation in occupational therapy education. Issue 3 (3rd July 2021) - de Jong, Daniela Castro; Pike, Georgia; West, Susan; Valerius, Harley; Kay, Anne; Ellis, Stephanie
ABSTRACT: Music is a complex occupation, with multiple positive effects on health, occupational performance, collaboration, and socialisation. This educational discussion paper describes a 6-year collaboration between an occupational therapy program in a mid-sized Australian city and a socio-altruistic music program designed to empower all participants to engage in helping others through music. Within this transdisciplinary collaboration, singing with others is framed as both a co-occupation and a collective occupation, as participants share music and social contact through songs, voluntary movement, touch, and eye contact, for mutual well-being. The collaboration has engaged over 300 occupational therapy students in participation and facilitation of music making sessions in schools and nursing homes. Acknowledging occupational therapy's historical connections with the arts, the paper focuses on the collective narrative of academics and graduate occupational therapy students. The paper describes how shared music outreach sessions can provide students with opportunities to experience and value the complexity of co-occupations in both personal and professional terms. As graduates who have implemented some of the music program's approaches in subsequent employment in healthcare contexts, former students report positive interactions with clients, improvement in communication skills, doing-with-and-for-others as a key strategy in their practice, and valuing the use of the arts as a therapeutic occupation strategy.